Value of NT-proBNP and Galectin-3 as Biomarkers in the Follow-Up of Asymptomatic Elderly Patients with Severe Aortic Stenosis - Ramos, Mónica; Quezada Feijoó, Dolores Maribel; Ayala Muñoz, Rocío; Manzano, Ascensión; Gómez Pavón, Francisco Javier; Jaramillo Hidalgo, Javier; Herrera, Cristina; López Vazquez de la Torre, Mariola; Toro, Rocío (My University, 2023)
Recognizing symptoms in elderly patients with severe aortic stenosis (AS) can be a chal lenge. Serum biomarkers such as Galectin-3 or N-terminal prohormone B-type natriuretic peptide (NT-proBNP) are involved in remodeling and heart failure (HF) development and could support the diagnosis of AS. We set out to test the usefulness of NT-proBNP and Galectin-3 in predicting events in this population. We designed a prospective observational case¿control study, including 50 asymptomatic patients older than 70 years, diagnosed with severe degenerative AS, and 50 con trol individuals. The NT-proBNP and Galectin-3 levels were measured. A follow-up was carried out at 12 months to determine the occurrence of hospital admission for HF, all-cause mortality or the appearance of symptoms. The patients with severe AS had higher Galectin-3 and NT-proBNP concentrations. The area under the receiver operating characteristic curve of the NT-proBNP was 0.812 (95% CI, 0.646¿0.832), and that of the Galectin-3 was 0.633 (95% CI, 0.711¿0.913). NT-proBNP was a good predictor of events [HR 3.45 (95% CI 1.32¿9.03), p = 0.011]. A Kaplan¿Meier analysis showed that the probability of freedom from events was significant in patients who exhibited a combination of higher NT-proBNP and Galectin-3 levels (log-rank p = 0.032). Therefore, NT-proBNP was the most reliable predictor of events in asymptomatic patients with severe AS. A combination of NT-proBNP and Galectin-3 levels may be vital in the clinical follow-up of these patients and in the decision-making process. Keywords: aortic stenosis; older patients; congestive heart failure; Galectin-3; NT-proBNP